Siirt Pistachio as a Geographical Indication Candidate in the Urban Branding Process - Demir, Doğan; Yücel, Nurcan (Siirt University, 2024)
Although Siirt province is very rich in terms of local products and tourism potential, it has not sufficiently created brand awareness and strategy for promotion. Cities have to compete in order to become centers of attraction. Geographical indications are important in this competition. Siirt province, which has 5 geographical indications in the urban branding process, has not yet registered Siirt Pistachio, which is identified with its name, as a geographical indication. Studies on Siirt pistachio in recent years, news on the internet and in the media have been analyzed and suggestions have been made for Siirt pistachio to reach the values it deserves.

Siirt ili, yerel ürünler ve turizm potansiyeli açısından oldukça zengin olmasına rağmen tanıtıma yönelik marka bilinci ve stratejisini yeterince oluşturamamıştır. Kentler, cazibe merkezi olabilmek için rekabet içinde olmak zorundadırlar. Bu rekabette coğrafi işaretler önem arz etmektedir. Kentsel markalaşma sürecinde 5 adet coğrafi işarete sahip olan Siirt ili, kendi adıyla özdeşleşen Siirt Fıstığını bir coğrafi işaret olarak henüz tescil ettirememiştir. Siirt fıstığıyla ilgili son yıllarda yapılmış olan çalışmalar, internet ve medyada geçen haberler incelenerek Siirt fıstığının hak ettiği değerlere ulaşabilmesi için önerilerde bulunulmuştur.
Kentsel Markalaşma Sürecinde Coğrafi İşaret Adayı Olarak Siirt Fıstığı
Keywords: Marketing (Other); Pazarlama (Diğer)